Alienation and Displacement in the Novels of Manju Kapur: Exploring Alienation and Displacement in Manju Kapur's Novels (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The predicament of belongingness in the novels of the creators referenced above, especially in Manju Kapur's novels involves transition and misery, which further uncovers the issues of ethnic identity, social identity and the vulnerabilities of remaining in one area. The paper means to unveil the hero's feeling of distance and dislodging in Canada in one of the Kapur's novels The Immigrant where the creator ventures life as an immigrant was horrendous, compelling the people to put forth an attempt to experience the procedure of economic, social and social alteration. Manju Kapur's The Immigrant is the narrative of Dislocation and Cultural clash is an Ethic Diaspora Novel. It is around thirty one year old maid, Nina, who lived with her bereft mother in Delhi. She gets married with Ananda, a NRI, Dentist and fly to Canada to begin her new life. Manju Kapur is one of the obvious Indian English authors who has attempted to outline the sexual orientation issues annoying lady all in all and Indian lady specifically.